The Effect of Good Corporate Governance Mechanism on Earnings Management - Zaqiatus Sholiha (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
The purpose of this study is to analyze the effect of Good Corporate Governance (GCG) on earnings management. Good Corporate Governance (GCG) is represented by the size of the board of commissioners, the composition of the independent board of commissioners and the size of the audit committee, while for earnings management, it is measured by discretionary accruals. This study uses a population in the form of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018 and 2019. The sample was selected by purposive sampling method, the criteria were manufacturing companies engaged in the consumer good industry sub-sector and produced 84 companies as research samples. The method of testing the hypothesis is done by using multiple linear regression method. The results of this study indicate that the size of the board of commissioners, the composition of the independent commissioner board and the size of the audit committee have an effect on earnings management.